Case report: Post-thoracic surgery acquired venous thoracic outlet syndrome - Mansouri, Mohamed Amine; Lutz, Jon Andri (Frontiers in Surgery, 2023)
Thoracic outlet syndrome (TOS) is a rare entity responsible for the vascular and/or nervous symptoms of the upper limbs. Unlike the congenital anatomical anomalies that cause TOS, acquired etiologies are even less common. Here, we report the case of a 41-year-old male with iatrogenic acquired TOS secondary to complex chest wall surgery for chondrosarcoma of the manubrium sterni; he was diagnosed with chondrosarcoma of the manubrium sterni in November, 2021. After staging was completed, primary surgery was performed. The operation was complex, with en-bloc resection of the manubrium sterni; the upper part of the corpus sterni; the first, second, and third bilateral parasternal ribs; and the medial clavicles, whose stumps were fixed on the first ribs. We reconstructed the defect using a double Prolene mesh, and bridged the second and third ribs on each side using two screwed plates. Finally, the wound was covered with pediculated musculocutaneous flaps. A few days after the operation, the patient presented with swelling in the left upper limb. Doppler ultrasound revealed slowing-down of the left subclavian vein flow, which was confirmed via thoracic computed tomography angiography. Systemic anticoagulation was initiated, and the patient began rehabilitation physiotherapy six weeks postoperatively. Symptoms had resolved by the 8-week outpatient follow-up, and anticoagulation therapy was stopped at three months; radiological follow-up demonstrated an improvement in subclavian vein flow without thrombosis. To the best of our knowledge, this is the first description of acquired venous TOS after thoracic surgery. Conservative treatment was found to sufficiently avoid the need for more invasive methods.